Stanisław Staszic - a Sympathizer of Łódź (1755–1862) - Domański, Czesław (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Stanisław Staszic was born on 6 November, 1755 in Piła a to a wealthy middle class family. Staszic played an important role in the development of Polish industry, working at the same time as a geologist and studying nature (in 1825 he published information about the Izerskie and Karkonosze Mountains). In the years 1816–1824 he held the post of the director general of Department of Industry and Crafts of the Congress Kingdom. At that time he devised a plan for redevelopment of the  Industrial Region of Old Poland and, after he had founded in 1816 the Hrubieszow Agricultural Society, he became one of the pioneers of the peasant cooperative movement. He resumed exploitation of coal from the Reden deposit located in the present day Dąbrowa Górnicza. On his initiative a lot of industrial buildings were erected e.g. the first tin smelting works in the Kingdom of Poland (4 smelting works under one name of  "Konstanty" – 1816–1822) and iron ore metallurgy centres. He also wrote a poem entitled “The Human Race 1919–1920”.